2015
DOI: 10.1016/j.chembiol.2015.05.008
|View full text |Cite
|
Sign up to set email alerts
|

Growth Factor Identity Is Encoded by Discrete Coiled-Coil Rotamers in the EGFR Juxtamembrane Region

Abstract: Summary Binding of the growth factor TGF-α to the EGFR extracellular domain is encoded through the formation of a unique anti-parallel coiled coil within the juxtamembrane segment. This new coiled coil is an ‘inside-out’ version of the coiled coil formed in the presence of EGF. A third, intermediary coiled coil interface is formed in the juxtamembrane segment when EGFR is stimulated with betacellulin. The seven growth factors that activate EGFR in mammalian systems (EGF, TGF-α, epigen, epiregulin, betacellulin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
84
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(93 citation statements)
references
References 46 publications
8
84
1
Order By: Relevance
“…JMA regions of EGFR are shown to be helical by the number of studies, 4,12,18 and the conformation of the JMA-JMA dimer was even found to be dependent on the type of EGFR ligand. 19 Besides, we suppose that the observed ability of the membrane environment to govern the helicity and membrane binding propensity of the EGFR JMA domains may indicate that cellular membranes can play an active role in the EGFR activation process.…”
Section: * S Supporting Informationmentioning
confidence: 98%
“…JMA regions of EGFR are shown to be helical by the number of studies, 4,12,18 and the conformation of the JMA-JMA dimer was even found to be dependent on the type of EGFR ligand. 19 Besides, we suppose that the observed ability of the membrane environment to govern the helicity and membrane binding propensity of the EGFR JMA domains may indicate that cellular membranes can play an active role in the EGFR activation process.…”
Section: * S Supporting Informationmentioning
confidence: 98%
“…A variety of extracellular or intracellular ligands of paracrine or autocrine origin -including epidermal growth factor (EGF), transforming growth factor alpha (TGF-a), betacellulin, amphiregulin, epigen, epiregulin and heparin binding EGF-like growth factor-bind to the surface region of the receptor [30]. Ligand binding leads to receptor dimerization due to intermolecular interactions (critical dimerization of domain II with the exception of a truncated sEGFR (sEGFR501) that remain monomeric [31].…”
Section: Introducing the Egfr: Gene/protein Structure And Functionmentioning
confidence: 99%
“…Further, it is also unclear how different extracellular growth factors can induce discrete intracellular responses including receptor downregulation versus receptor recycling, all of which are mediated through EGFR signaling. Because EGFR must somehow elicit distinct responses that are contingent upon the extracellular stimuli, Schepartz and colleagues used a clever approach to specifically interrogate changes in the juxtamembrane (JM) region of EGFR in response to various stimuli as a possible mechanism for translating these intracellular messages (Doerner et al, 2015; Figure 1). …”
mentioning
confidence: 98%
“…Exactly how ligand binding is translated into specific signaling outcomes remains incompletely understood. In this issue, Doerner et al (2015) provide insights into a role that the juxtamembrane (JM) region of a representative ErbB kinase, EGFR, plays in this process.…”
mentioning
confidence: 99%
See 1 more Smart Citation